2017
DOI: 10.3892/etm.2017.5419
|View full text |Cite
|
Sign up to set email alerts
|

A novel three‑dimensional tumorsphere culture system for the efficient and low‑cost enrichment of cancer stem cells with natural polymers

Abstract: Cancer stem cells (CSCs) are considered to serve a key role in tumor progression, recurrence and metastasis. Tumorsphere culture is the most important method for enriching CSCs and is widely used in basic research and drug screening. However, the traditional suspension cell culture system has several disadvantages, including low efficiency, high cost and difficult procedure, making it difficult to produce tumorspheres on a large scale. In the present study, two biomaterials, methylcellulose (MC) and gellan gum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In vitro tumor-sphere formation is a new and inexpensive method considered a potential alternative for in vivo experiments and is now frequently used for the screening of anticancer drugs. 17 In the present study, the number and size of tumor spheres were sharply reduced by PEF-III treatment in a concentration-dependent manner. The mRNA profile of PEF-III-treated tumor-sphere cells showed that PEF-III treatment clearly suppressed the proliferation gene and expression of metastasis-modulating genes.…”
Section: Discussionsupporting
confidence: 55%
“…In vitro tumor-sphere formation is a new and inexpensive method considered a potential alternative for in vivo experiments and is now frequently used for the screening of anticancer drugs. 17 In the present study, the number and size of tumor spheres were sharply reduced by PEF-III treatment in a concentration-dependent manner. The mRNA profile of PEF-III-treated tumor-sphere cells showed that PEF-III treatment clearly suppressed the proliferation gene and expression of metastasis-modulating genes.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that tumorsphere culture system provides a useful method for maintaining a CSC microenvironment [18]. In this study, we enriched the cells having stem cell property in MCF-7 and BT-549 cell lines using tumorsphere formation assay.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, numerous challenges remain with the traditional suspension culture system. These include low yield and difficulty in maintaining spheroids and changing the media procedure [ 90 , 91 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, different scaffold-based 3D cell culture techniques that use various types of scaffolds have recently been reported to develop advanced methods for CSC enrichment. These include chitosan-alginate scaffolds [ 104 ], polyelectrolyte multilayer films [ 105 ], hyaluronic acid-based multilayer films [ 106 ], porous chitosan-alginate scaffolds [ 107 ], poly (ε-caprolactone) scaffolds [ 108 ], Matrigel ® [ 109 ], agarose multi-well dishes [ 110 ], methylcellulose and gellan gum [ 103 ], and hyaluronic acid hydrogels [ 111 ]. Despite recent advancements in CSC-enrichment techniques, improving the methods for enrichment of the desired CSCs remains an important challenge.…”
Section: Discussionmentioning
confidence: 99%